Change in plasma membrane potential of rat thymocytes by tert-butylhydroquinone, a food additive: Possible risk on lymphocytes. (November 2017) - Takeda, Maki; Oyama, Keisuke; Kamemura, Norio; Kanemaru, Kaori; Yuasa, Keizo; Yokoigawa, Kumio; Oyama, Yasuo
Abstract: Tertiary butylhydroquinone (TBHQ) is a food additive and has various beneficial actions under in vitro and in vivo experimental conditions. Therefore, it is necessary to collect additional data on the toxicity of TBHQ in order to avoid adverse effects during clinical applications. Changes in plasma membrane potential are associated with changes in physiological functions even in non-excitable cells such as lymphocytes. Thus, compounds that affect membrane potential may modify some lymphocytic functions. The effect of TBHQ on plasma membrane potential was examined in rat thymocytes using flow cytometric techniques. Treatment of rat thymocytes with TBHQ caused hyperpolarization and then depolarization. The TBHQ-induced hyperpolarization was due to the activation of Ca 2+ -dependent K + channels. TBHQ elevated intracellular Ca 2+ levels. The depolarization by TBHQ was caused by a nonspecific increase in membrane ionic permeability. Both the sustained depolarization and elevation of intracellular Ca 2+ level by TBHQ are thought to be adverse for thymocytes because such changes disturb membrane and intracellular signaling. The thymus is most active during neonatal and pre-adolescent periods. If TBHQ exerts adverse actions on thymocytes, it may result in an immunotoxic effect in neonates and adolescents. Highlights: tert -Butylhydroquinone (TBHQ), a food additive, has therapeutic potential. TBHQ caused hyperpolarization that was followed by depolarization in rat thymocytes. The hyperpolarization was due to the activation of Ca 2+ -dependent K + channels. The depolarization was due to a nonspecific increase in membrane ionic permeability. TBHQ-induced changes in membrane potential may be adverse for lymphocytes.